Visceral obesity and insulin resistance associate with CD36 deletion in lymphatic endothelial cells - Cifarelli, Vincenza; Appak-Baskoy, Sila; Peche, Vivek S.; Kluzak, Andrew; Shew, Trevor; Narendran, Ramkumar; Pietka, Kathryn M.; Cella, Marina; Walls, Curtis W.; Czepielewski, Rafael; Ivanov, Stoyan; Randolph, Gwendalyn J.; et al. (Nature Communications, 2021)
Disruption of lymphatic lipid transport is linked to obesity and type 2 diabetes (T2D), but regulation of lymphatic vessel function and its link to disease remain unclear. Here we show that intestinal lymphatic endothelial cells (LECs) have an increasing CD36 expression from lymphatic capillaries (lacteals) to collecting vessels, and that LEC CD36 regulates lymphatic integrity and optimizes lipid transport. Inducible deletion of CD36 in LECs in adult mice (Cd36ΔLEC) increases discontinuity of LEC VE-cadherin junctions in lacteals and collecting vessels. Cd36ΔLEC mice display slower transport of absorbed lipid, more permeable mesenteric lymphatics, accumulation of inflamed visceral fat and impaired glucose disposal. CD36 silencing in cultured LECs suppresses cell respiration, reduces VEGF-C-mediated VEGFR2/AKT phosphorylation and destabilizes VE-cadherin junctions. Thus, LEC CD36 optimizes lymphatic junctions and integrity of lymphatic lipid transport, and its loss in mice causes lymph leakage, visceral adiposity and glucose intolerance, phenotypes that increase risk of T2D.